Exploring medicines information needs of mental health service users at a New Zealand hospital. Issue 6 (3rd July 2022) - Sheed, Lucy; Haua, Robert; Honey, Michelle L. L.; Aspden, Trudi J.; Brackley, Kim E.; Chan, Amy H. Y.
ABSTRACT: Providing effective medicines information to individuals can improve outcomes, yet little is known about what information mental health service users need and want about their medicines, and how best to deliver this. The aim of this study was to explore the medicines information needs of mental health service users. Adults (n=30) under the care of acute mental health services in a New Zealand hospital were invited to take part in semi-structured interviews or a focus group to explore preferences for medicines information. Interview data were analysed using an inductive thematic approach. Six key themes were identified: 1) personalisation of information, 2) adverse and beneficial effects, 3) relationships and trust, 4) informed choice, 5) use of reliable internet resources and 6) involvement of family and support people. Preferences on content, timing, provider and format of information delivery were highly individualised indicating the need for information to be personalised to the needs of the service user. A trusted relationship with their healthcare provider was essential . Making informed decisions reduced confusion or fear about medicines. Understanding medicines information needs of patients can help improve the education health professionals provide on medicines, thus potentially improving patient engagement and outcomes.